Antistaphylococcal Triazole-Based Molecular Hybrids: Design, Synthesis and Activity - Kostiantyn Shabelnyk; Alina Fominichenko; Oleksii Antypenko; Olexandr Gaponov; Svitlana Koptieva; Svitlana Shyshkina; Oleksii Voskoboinik; Sergiy Okovytyy; Serhii Kovalenko; Valentyn Oksenych; Oleksandr Kamyshnyi (Pharmaceuticals)
Background: In the era of resistance, the design and search for new “small” molecules with a narrow spectrum of activity that target a protein or enzyme specific to a certain bacterium with high selectivity and minimal side effects remains an urgent problem of medicinal chemistry. In this regard, we developed and successfully implemented a strategy for the search for new hybrid molecules, namely, the not broadly known [2-(3-R-1H-[1,2,4]-triazol-5-yl)phenyl]amines. They can act as “building blocks” and allow for the introduction of certain structural motifs into the desired final products in order to enhance the antistaphylococcal effect. Methods: The “one-pot” synthesis of the latter is based on the conversion of substituted 4-hydrazinoquinazolines or substituted 2-aminobenzonitriles and carboxylic acid derivatives to the target products. The possible molecular mechanism of the synthesized compounds (DNA gyrase inhibitors) was investigated and discussed using molecular docking, and their further study for antistaphylococcal activity was substantiated. Results: A significant part of the obtained compounds showed high antibacterial activity against Staphylococcus aureus (MIC: 10.1–62.4 µM) and 5-bromo-2-(3-(furan-3-yl)-1H-1,2,4-triazol-5-yl)aniline and 5-fluoro-2-(3-(thiophen-3-yl)-1H-1,2,4-triazol-5-yl)aniline, with MICs of 5.2 and 6.1 µM, respectively, approaching the strength of the effect of the reference drug, “Ciprofloxacin” (MIC: 4.7 µM). The conducted SAR and ADME analyses confirm the prospects of the further structural modification of these compounds. The obtained [2-(3-R-1H-[1,2,4]-triazol-5-yl)phenyl]amines reveal significant antimicrobial activity and deserve further structural modification and detailed study as effective antistaphylococcal agents. The SAR analysis revealed that the presence of a cycloalkyl or electron-rich heterocyclic fragment in the third position of the triazole ring was essential for the antibacterial activity of the obtained compounds. At the same time, the introduction of a methyl group into the aniline moiety led to an enhancement of activity. The introduction of halogen into the aniline fragment has an ambiguous effect on the level of antistaphylococcal activity and depends on the nature of the substituent in the third position. Conclusions: Obtained [2-(3-R-1H-[1,2,4]-triazol-5-yl)phenyl]amines reveal significant antistaphylococcal activity and deserve for further detailed study as effective antibacterial agents.